Fidelity requirements in brushless permanent magnet motor modelling - Welford, John; Apsley, Judith M.; Forsyth, A.J.; Sophian, Ali (The Institution of Engineering and Technology (IET), 2012)
The paper discusses the development and validation of motor simulation models to aid in the design of actuators for use with automotive variable geometry turbochargers. The specific focus is on the benefit of increasing the fidelity of the motor model, against the tradeoff of increased complexity. Several separate models of the same brushless permanent magnet motorare developed and validated against measurements made from a sample motor. These results, along with the simulation time required for different types of model, are presented and used to draw conclusions on the appropriate fidelity of model for different types of analysis.